2015
DOI: 10.1084/jem.20142009
|View full text |Cite
|
Sign up to set email alerts
|

Functional loss of IκBε leads to NF-κB deregulation in aggressive chronic lymphocytic leukemia

Abstract: Mansouri et al. applied targeted deep sequencing to identify mutations within NF-κB core complex genes in CLL. NFKBIE, the gene encoding the inhibitory IκBε molecule, was most frequently mutated, especially in poor-prognostic subgroups of CLL. The authors show that NFKBIE mutations were associated with significantly reduced IkBε expression and p65 inhibition, ultimately leading to NF-κB activation and a more aggressive disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
82
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(89 citation statements)
references
References 33 publications
6
82
0
1
Order By: Relevance
“…Targeted deep sequencing of 18 genes constitutive of the NF-jB core complex identified also mutations in NFKB2, TNFAIP3, IKBR, and REL genes [99]. Frequent inactivating mutations, including a recurrent 4-bp deletion, of the NFKBIE gene, are seen in advanced stage CLL [73,99,100].…”
Section: Implication Of the Bcr Tlr Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Targeted deep sequencing of 18 genes constitutive of the NF-jB core complex identified also mutations in NFKB2, TNFAIP3, IKBR, and REL genes [99]. Frequent inactivating mutations, including a recurrent 4-bp deletion, of the NFKBIE gene, are seen in advanced stage CLL [73,99,100].…”
Section: Implication Of the Bcr Tlr Pathwaysmentioning
confidence: 99%
“…Frequent inactivating mutations, including a recurrent 4-bp deletion, of the NFKBIE gene, are seen in advanced stage CLL [73,99,100]. NFKBIE encodes a negative regulator of NFjB signaling in B cells, which is important for controlling the B-cell response to external stimuli, including TLR and BCR signaling [101].…”
Section: Implication Of the Bcr Tlr Pathwaysmentioning
confidence: 99%
“…ATM, NOTCH1, SF3B1, TP53) 13,14 with a long tail of genes altered in <5% of cases (e.g. CHD2 15 , MED12 16 , NFKBIE 17 , POT1 18 , RPS15 19 , SETD2 20 , XPO1 21 ). Though integration of molecular information has been proposed to improve classical risk stratification models [22][23][24][25] , a substantial proportion of patients with a dismal clinical course will not be captured by these algorithms, hence indicating a need to identify additional molecular markers of disease aggressiveness.…”
Section: Introductionmentioning
confidence: 99%
“…In CLL, besides TP53 and ATM mutations, which are both known to confer poor prognosis, recent high-throughput NGS studies have revealed recurrent mutations within NOTCH1, SF3B1, and BIRC3 for example, that were reported to be associated with poor clinical outcome with higher frequencies in relapsing/treatment-refractory CLL and in Richter's syndrome. 48,[69][70][71][72][73][74][75][76][77][78][79] More recent studies have also identified additional gene mutations that may confer a worse outcome in CLL, e.g. NKFBIE, EGR2, and RPS15, although they have been studied less.…”
Section: Genes With Prognostic Potentialmentioning
confidence: 99%
“…NKFBIE, EGR2, and RPS15, although they have been studied less. [78][79] In a recent multicenter study conducted within ERIC, sequencing of TP53, NOTCH1, SF3B1, BIRC3 and MYD88 was performed in a large patient series (totaling 3,490 patients), revealing that TP53 and SF3B1 mutations, but not NOTCH1 mutations, remained as independent prognostic markers of shorter time to first treatment in multivariate analysis, even amongst patients expressing unmutated IGHV genes. 50 A few published clinical trials have also pointed to a prognostic and even predictive role of SF3B1 and NOTCH1 mutations in CLL, 28 where, in particular, the latter confers resistance to the anti-CD20 monoclonal antibodies rituximab 29 and ofatumumab, 80 however, this needs further exploration and validation.…”
Section: Genes With Prognostic Potentialmentioning
confidence: 99%